Transient facial nerve palsy after scalp block for awake craniotomy: A case report (Indian Journal of Case Reports, 2018)
Awake craniotomy is a unique clinical setting that needs anesthesiologist to provide variable states of sedation and analgesia to ensure optimal operating conditions without compromising patient safety. Scalp block is an integral part of awake craniotomy as it provides regional anesthesia to the nerves innervating the scalp. It minimizes response to noxious stimuli of cranial pin application and craniotomy. We report a case of transient facial nerve palsy after scalp block in awake craniotomy in a patient with a lesion in the motor cortex. Facial nerve palsy has been described as a rare complication of scalp block and is less reported.